A new species of Utivarachna Kishida, 1940 from Fanjing Mountain Nature Reserve, Guizhou, China (Araneae: Trachelidae) - Li, Haibo; He, Yongyan; Zhang, Jianshuang; Yu, Hao (Zootaxa, 2022)
A new species belonging to the kinabaluensis group of the trachelid genus Utivarachna Kishida, 1940, U. fanjing sp. nov., is described from southwestern China. Detailed description, diagnosis, photographs and distribution map of the new species are given. DNA barcodes (a partial fragment of the mitochondrial cytochrome oxidase subunit I gene, COI) of the species were obtained to confirm matching of the sexes and for future use in molecular studies.